KULIAH KERJA NYATA (KKN) TEMATIK PENGEMBANGAN POTENSI INDUSTRI UMKM DAN SUMBER DAYA MANUSIA BERBASIS DIGITAL - Abid Muhammad Asfar; Shafiera Lazuarni; Lukita Tripermata; Roswaty (Politeknik Negeri Sriwijaya, 2022)
Thematic Community Service Program, Faculty of Economics, Indo Global Mandiri University is carried out with the aim that students are able to apply the fields of study that have been taken during the education period, so that they can train students' mentality naturally before going directly into the real world of work. Through this thematic KKN students are able to adapt directly to situations, circumstances, risks and students are required to be responsible for all activities that take place during the KKN period.